Diseño de la estructura organizacional de la empresa asociación almacén comunitario Cxha Cxha Wala (Asowala) (2020)
This degree work presents the design and organizational structure proposal that was made for the Cxha Cxha Wala Community Warehouse Association Company (ASOWALA) and thus be able to contribute to its growth, as well as to competitive and profitable development. Consequently, and taking into account the administrative perspective of the work, theories and administrative foundations were gathered, as well as research methods and techniques, in order to present the appropriate design to meet the need for strategic planning of the company. In order to obtain the data and all the information necessary for the diagnosis of the company and identify its needs, in such a way that the correct strategy will be established, a structured survey and interview were carried out. In addition, analysis tools such as the PESTEL and the EFI matrix were implemented to complement the situational diagnostic report of the company and the sector where it carries out its economic activity, thus identifying the market threats in order to mitigate them with the opportunities that they appear in the micro and macro environment. Next, by means of an interview to the personnel for the analysis of positions, the functions, competencies and responsibilities of each position were defined to distribute the workload, enhance the performance and productivity of the company, and strengthen all the processes carried out within from ASOWALA. The organizational chart that will be part of the new organizational design of the company was also designed to contribute to its competitive development. The research was carried out in the municipality of Santander de Quilichao, the company ASOWALA was chosen as a reference for future research on indigenous companies and organizations in the country and as a design and organizational structure appropriate to the purposes and goals of The company can achieve productive, profitable and competitive growth of all organizations.